2018
DOI: 10.3389/fchem.2018.00390
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Anionic Surfactant Sodium Dodecylbenzene Sulfonate on the Surface of Montmorillonite Minerals

Abstract: The adsorption characteristics of sodium dodecylbenzene sulfonate (SDBS) on the surface of montmorillonite can lay a foundation for obtaining the optimum concentration of the anionic surfactant. The best absorption wavelength of SDBS was determined using an ultraviolet spectrophotometer. The standard curves of concentration and absorbance of SDBS were established. The amount of SDBS adsorbed on the surface of montmorillonite at various concentrations was calculated by stirring adsorption method. Scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…The adsorption capacity increased with the increase of temperature; perhaps the reason was that the MMIPs could be swollen easily under higher temperature so that more binding sites were exposed. Thus, the adsorption capacity at a higher temperature was greater than that at low temperature, which is consistent with the results of relevant literature [28,30,40].…”
Section: Resultssupporting
confidence: 92%
“…The adsorption capacity increased with the increase of temperature; perhaps the reason was that the MMIPs could be swollen easily under higher temperature so that more binding sites were exposed. Thus, the adsorption capacity at a higher temperature was greater than that at low temperature, which is consistent with the results of relevant literature [28,30,40].…”
Section: Resultssupporting
confidence: 92%
“…The upper clear solution was filtered after stirring for 0 min, 20 min, 40 min, 60 min, 90 min, and 120 min, respectively, then the absorbance of the filtrate was measured by 201 UV spectrophotometer (The test wavelength of the ultraviolet spectrophotometer ranged from 190 to 1100 nm and the wavelength accuracy was ± 0.8 nm). Adsorptive capacity calculation The absorbance peak of SDBS occurs at about 223 nm, and when the solution concentration is 3–5 mmol/L, the absorbance peak has a good linear relationship with the concentration of SDBS 5 : where, C is concentration of SDBS, mmol/L; A represents the peak wavelength of absorbance. According to the absorbance test results of filtered filtrate, in combination with formula ( 1 ), the adsorptive capacity can be calculated as follows: where, q t is the adsorptive capacity at time t , mmol/g; C 0 represents the initial concentration, mmol/L; C t is the concentration at time t , mmol/L; V is the volume of the solution, L; m is the mass of the kaolinite, g. Determination of the adsorptive behaviour of kaolinite to SDBS The adsorptive behaviour of kaolinite to SDBS was investigated mainly by comparing the adsorption process with the classical adsorption kinetic model.…”
Section: Methodsmentioning
confidence: 99%
“…According to the absorbance test results of filtered filtrate, in combination with formula ( 1 ), the adsorptive capacity can be calculated as follows: where, q t is the adsorptive capacity at time t , mmol/g; C 0 represents the initial concentration, mmol/L; C t is the concentration at time t , mmol/L; V is the volume of the solution, L; m is the mass of the kaolinite, g. Determination of the adsorptive behaviour of kaolinite to SDBS The adsorptive behaviour of kaolinite to SDBS was investigated mainly by comparing the adsorption process with the classical adsorption kinetic model. Wherein, the fitting formula of pseudo-first-order adsorption dynamics equation to characterise physical adsorption is as follows 5 : where, q e is the equilibrium absorption capacity, mmol/g; k 1 is the first-order adsorption constant, min −1 . The fitting formula of pseudo-second-order kinetic model to characterise chemical adsorption is as follows 5 : where, k 2 is the second-order adsorption constant, g·mmol −1 ·min −1 ; k 2 q e 2 is the initial adsorption time, mmol·g −1 ·min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proper oil phase can make the interface SDBS and its isomers more compact and orderly, providing better interfacial activity. Ni et al (2018) investigated the adsorption characteristics of anionic surfactant sodium dodecylbenzene sulfonate on the surface of montmorillonite minerals. It showed that the addition of H+ to the SDBS solution could reduce electrostatic repulsion and promote the adsorption of SDBS on montmorillonite.…”
Section: Application Of Molecular Dynamics Simulations For Research Imentioning
confidence: 99%